Determinan curahan jam kerja sektor publik perempuan pedagang bunga di pasar bunga Taman Sari - Dewi, Ni Putu Nia Kharisma; Marhaeni, Anak Agung Istri Ngurah (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
The purpose of this study is to analyze the simultaneous and partial influence of the number of consumers, women's contribution to family income, socio-economic conditions, the concept of work in Hinduism, and the intensity of traditional activities on the outpouring of working hours of female flower traders at Taman Sari Flower Market. Also, to analyze the role of the intensity of traditional activities in moderating the influence of the concept of work in Hinduism on the outpouring of working hours of female flower traders at Taman Sari Flower Market. The number of samples was 77 female flower traders. The design of this study used a quantitative approach in the form of associative. Data were collected using observation and interview methods, data analysis was carried out using moderated regression analysis. The results showed that all factors, including the number of consumers, women's contribution to household income, socio-economic conditions, the concept of work in Hinduism, and the intensity of traditional activities, had a positive and significant impact on the working hours of female flower traders. It can be concluded that the higher the factors that affect the outpouring of working hours, the working hours will increase, and vice versa.